An inconvenient truth about the banana industry in Asia - Joven, B. (FFTC, 2014)
The deadly Fusarium wilt (Panama wilt) Tropical Race 4 (TR4) disease has long emerged in China, Indonesia, Malaysia, Taiwan, and the Philippines. But of late, aggressive spread has been reported specifically in the Philippines and China, two major Cavendish producers in the world.This was an alarming revelation during the consultation-workshop on the ”Socio-economic Impacts of Fusarium Wilt Disease of Cavendish Banana in the Asia-Pacific Region” that was organized by the Food and Fertilizer Technology Center (FFTC), Philippine Council for Agriculture, Aquatic and Natural Resources Research and Development (PCAARRD), and the Banana Asia Pacific Network (BAPNET)-Bioversity International.